2017
DOI: 10.1167/17.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Elevated arousal levels enhance contrast perception

Abstract: Our state of arousal fluctuates from moment to moment-fluctuations that can have profound impacts on behavior. Arousal has been proposed to play a powerful, widespread role in the brain, influencing processes as far ranging as perception, memory, learning, and decision making. Although arousal clearly plays a critical role in modulating behavior, the mechanisms underlying this modulation remain poorly understood. To address this knowledge gap, we examined the modulatory role of arousal on one of the cornerston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…Recent studies in mice have characterized effects of arousal on stimulus responses at various stages of the visual system, including V1, lateral geniculate nucleus, superior colliculus, and retina [65][66][67][68]. Few studies have investigated the impact of arousal on visual responses in humans [69][70][71]. Our study was designed to minimize the impact of the visual stimulus.…”
Section: Effect Of Arousal On Stimulus-evoked Activitymentioning
confidence: 99%
“…Recent studies in mice have characterized effects of arousal on stimulus responses at various stages of the visual system, including V1, lateral geniculate nucleus, superior colliculus, and retina [65][66][67][68]. Few studies have investigated the impact of arousal on visual responses in humans [69][70][71]. Our study was designed to minimize the impact of the visual stimulus.…”
Section: Effect Of Arousal On Stimulus-evoked Activitymentioning
confidence: 99%
“…Although lower-level visual cortical areas do not belong to the pain network, previous studies have shown that lower-level visual processes, such as contrast perception, are affected by arousal or emotion. 27,32 In particular, our results showed that there were positive correlations between lower-level visual cortical activation and pain ratings. It is also well known that attention modulates V1.…”
Section: Discussionmentioning
confidence: 51%
“…An oriented Gabor patch at fixation (subtending 4° of visual angle, 1 c/°) was generated on a gamma-corrected, PROPixx DLP LED projector (75-Hz refresh). 27 All aspects of the experiment-display generation, trial sequences, and staircase procedure were controlled using MATLAB and the Psychphysics Toolbox running on a MacBook Pro. 28 For each trial, one of 16 possible orientations, from 10° to 180° at 10° intervals except for 90° and 180°, was randomly selected.…”
Section: Methodsmentioning
confidence: 99%
“…By the same token, olfactory-visual interaction is presumably built in “hard-wiring” of the nervous system as an innate behavior ( Mayer, 1963 ; Herrnstein, 1972 ). One might assume that the olfactory stimulations affected not motion perception but just participants’ arousal level, which caused the different sense of visual perception ( Cano et al, 2006 ; Lee et al, 2014 ; Kim et al, 2017 ). To check that possibility, we measured fMRI activities in the thalamus that are associated with the level of arousal ( Portas et al, 1998 ; Cano et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%